The Influence of Transformational Leadership and Work Motivation on Employee Performance at PT Bank Sulteng Palu - Yapi, Stipi; Natsir, Syahir; Hasanuddin, Bakri; Murad, Moh Ali (Universitas Muhammadiyah Pontianak, 2026)
Based on the results of research using a quantitative approach to 49 respondents of PT Bank Sulteng Palu employees, it can be concluded that transformational leadership does not have a significant effect on employee performance, while work motivation has a positive and significant effect on employee performance. Simultaneously, both variables have a significant effect on performance, indicating that work motivation has a dominant role in improving employee performance, while the application of transformational leadership needs to be further strengthened in order to provide a more optimal positive influence in supporting the achievement of organizational performance. Keywords: Transformational Leadership; Work Motivation; Employee Performance Bank Sulteng Palu